Mechanistic insights into antiretroviral drug‐induced liver injury - Jamie N. Pillaye; Mohlopheni J. Marakalala; Nonhlanhla Khumalo; Wendy Spearman; Hlumani Ndlovu (Wiley, 2020)
Abstract All classes of antiretroviral therapy (ART) have been implicated to induce adverse drug reactions such drug‐induced liver injury (DILI) and immune‐mediated adverse reactions in Human Immunodeficiency Virus (HIV) infected individuals. Patients that develop adverse drug reactions tend to have prolonged stays in hospital and may require to change to alternative regimens if reactions persist upon rechallenge or if rechallenge is contraindicated due to severity of the adverse reaction. Diagnosis of DILI remains a huge obstacle that delays timely interventions, since it is still based largely on exclusion of other causes. There is an urgent need to develop robust diagnostic and predictive biomarkers that could be used alongside the available tools (biopsy, imaging, and serological tests for liver enzymes) to give a specific diagnosis of DILI. Crucial to this is also achieving consensus in the definition of DILI so that robust studies can be undertaken. Importantly, it is crucial that we gain deeper insights into the mechanism of DILI so that patients can receive appropriate management. In general, it has been demonstrated that the mechanism of ART‐induced liver injury is driven by four main mechanisms: mitochondrial toxicity, metabolic host‐mediated injury, immune reconstitution, and hypersensitivity reactions. The focus of this review is to discuss the type and phenotypes of DILI that are caused by the first line ART regimens. Furthermore, we will summarize recent studies that have elucidated the cellular and molecular mechanisms of DILI both in vivo and in vitro.